The Effectiveness of Psychological Well-Being Psychoeducation on Career Anxiety in Vocational High School Students Based on Gender - Putra, Surya Jaya Purnama; Suroso; Farid, Muhammad (Jurnal Multidisiplin Madani, 2024)
This study aims to prove the effectiveness of psychological well-being psychoeducation on career anxiety in vocational school students based on gender. This study is experimental research with one group pretest-posttest design. The results of the Wilcoxon Signed Rank Test analysis obtained a Z value = 2,646 (p < 0,05). This shows that psychological well-being psychoeducation is effective in reducing career anxiety in vocational school students. The results of the Mann-Whitney Test analysis at the pretest obtained a Z value = 0,182 (p > 0,05). While at the posttest obtained a Z value = 0,109 (p > 0,05). This means that there is no difference in the level of career anxiety between male and female students